Music and the Making of Portugal and Spain Nationalism and Identity Politics in the Iberian Peninsula (University of Illinois Press, 2023)
How music embodies and contributes to historical and contemporary nationalism What does music in Portugal and Spain reveal about the relationship between national and regional identity building? How do various actors use music to advance nationalism? How have state and international heritage regimes contributed to nationalist and regionalist projects? In this collection, contributors explore these and other essential questions from a range of interdisciplinary vantage points. The essays pay particular attention to the role played by the state in deciding what music represents Portuguese or Spanish identity. Case studies examine many aspects of the issue, including local recording networks, so-called national style in popular music, and music's role in both political protest and heritage regimes. Topics include the ways the Salazar and Franco regimes adapted music to align with their ideological agendas; the twenty-first-century impact of UNESCO's Intangible Cultural Heritage program on some of Portugal and Spain's expressive practices; and the tensions that arise between institutions and community in creating and recreating meanings and identity around music. Contributors: Ricardo Andrade, Vera Marques Alves, Salwa El-Shawan Castelo-Branco, Cristina Sánchez-Carretero, José Hugo Pires Castro, Paulo Ferreira de Castro, Fernán del Val, Héctor Fouce, Diego García-Peinazo, Leonor Losa, Josep Martí, Eva Moreda Rodríguez, Pedro Russo Moreira, Cristina Cruces Roldán, and Igor Contreras Zubillaga